A NOVEL DEAD-TIME ELIMINATION STRATEGY FOR VOLTAGE SOURCE INVERTERS IN INDUCTION HEATING SYSTEMS THROUGH FRACTIONAL ORDER CONTROLLERS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The voltage source inverter (VSI) based induction-heating systems consisting of full-bridge series resonant inverters use power switching devices such as the insulated-gate-bipolar-transistor (IGBT) to achieve zero current switching or zero voltage switching operation. Such a configuration is susceptible to shoot-through during switching periods and avoidance of shoot-through is achieved through the introduction of the dead time in general. However, it necessitates the inclusion of dead-time compensators to eliminate the adverse effects of the dead time. This paper proposes a novel voltage source inverter dead-time compensation strategy for induction heating systems that uses the fractional order proportional integral derivative (FOPID) controller. Although the integer-order proportional integral derivative (IOPID) controller is widely used for induction heating systems, it does not remove the impact of dead time and does not act as a compensator. The study covers the design and optimal tuning of the fractional order PID controller for the VSI fitted induction-heating system using fuzzy logic and compares the performance of the fuzzy FOPID controller with the standard IOPID controller. The simulations and corresponding results confirm that the fuzzy FOPID controller can appropriately compensate for the dead-time impact and can be considered a suitable control strategy for such induction heating systems. Modeling and simulations have been performed using MATLAB/ SIMULINK.
Keywords: Dead-time; Full bridge series resonant inverter; Fuzzy control; Fractional order proportional integral derivative; Induction heating; Voltage source inverter; Zero voltage switching